Stainless steel sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202580023186.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-30
AI Technical Summary
另一方面,已知马氏体系不锈钢钢板的强度高,相应地延性和韧性低
[0072]根据本发明,能够得到包含马氏体和奥氏体相且强度延性平衡和韧性优异的不锈钢钢板。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to stainless steel plates and methods for manufacturing the same. Background Technology
[0002] Martensitic stainless steel sheets possess excellent strength and are therefore used in automotive parts, among other applications. However, it is known that while martensitic stainless steel sheets have high strength, they also exhibit low ductility and toughness. Therefore, for example, as shown in Patent Document 1, a stainless steel material with a microstructure that controls the presence of austenitic phases in addition to martensite has been developed, improving the balance between strength and ductility, resulting in excellent properties in both areas.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-86405 Summary of the Invention
[0006] The problem the invention aims to solve
[0007] However, in the stainless steel sheet disclosed in Patent Document 1, there is room for further improvement in terms of improving the balance between strength and ductility (hereinafter also referred to as "strength-ductility balance") and improving toughness. Therefore, the object of the present invention is to provide a stainless steel sheet containing martensite and austenite phases that has excellent strength-ductility balance and toughness.
[0008] Solution for solving the problem
[0009] The present invention was made to solve the above-mentioned problems, and its main purpose is the stainless steel plate and the method of manufacturing the same.
[0010] (1) A stainless steel plate, the chemical composition of which is expressed as (in mass%) as follows:
[0011] C: 0.005~0.200%
[0012] Si: 0.05~2.50%
[0013] Mn: 0.1~8.0%,
[0014] P: Below 0.0800%
[0015] S: Below 0.030%
[0016] Cr: 12.0~20.0%
[0017] Ni: ≥0.30% and <8.00%
[0018] Mo: 0.01~1.00%
[0019] Al: Below 0.500%
[0020] N: 0.005~0.100%
[0021] Ca: 0~0.0100%
[0022] Cu: 0~7.0%,
[0023] Ti: 0~0.70%,
[0024] Nb: 0~1.00%
[0025] B: 0~0.0050%
[0026] V: 0~0.50%,
[0027] Sn: 0~0.10%
[0028] Co: 0~0.30%,
[0029] Balance: Fe and impurities,
[0030] The Cr equivalent calculated by equation (i) below is 10.0~20.0%.
[0031] The Ni equivalent calculated by equation (ii) below is 5.0% to 15.0%.
[0032] The Ms point calculated by equation (iii) below is above 50℃.
[0033] The metallographic structure contains martensite and austenite phases.
[0034] The area fraction of the austenite phase is greater than 30% and less than 100%.
[0035] The average grain size of the austenitic phase is less than 2.0 μm.
[0036] Cr equivalent (%) = Cr + Mo + 1.5Si + (0.5Nb)…(i)
[0037] Ni equivalent (%) = Ni + 30(C + N) + 0.5Mn + (0.3Cu)...(ii)
[0038] Ms point (℃)=545-330(C+N)+Al+7Co-14Cr-13C-23Mn-5Mo-4Nb-13Ni-7Si+3Ti+4V…(iii)
[0039] In the above formula, the symbols of each element represent the content (mass%) of each element contained in the stainless steel plate, and are set to zero if the element is not contained.
[0040] (2) The stainless steel plate according to (1) above, wherein,
[0041] The chemical composition, expressed in % by mass, contains ingredients selected from...
[0042] Ca: 0.0001~0.0100%
[0043] Cu: 0.5~7.0%,
[0044] Ti: 0.05~0.70%,
[0045] Nb: 0.01~1.00%
[0046] B: 0.0005~0.0050%
[0047] V: 0.01~0.50%,
[0048] Sn: 0.02~0.10%, and
[0049] Co: 0.01% to 0.30% of one or more of the following.
[0050] (3) The stainless steel plate according to (1) or (2) above, wherein,
[0051] The area fraction of the austenitic phase is over 85%.
[0052] (4) A method for manufacturing a stainless steel plate, comprising the following steps in sequence:
[0053] (a) A process of heating a slab having the chemical composition described in (1) or (2) above in the range of 1100 to 1300 degrees Celsius and hot rolling it to produce a hot-rolled steel plate.
[0054] (b) The hot-rolled steel plate annealing process is carried out as follows: the hot-rolled steel plate is held at an annealing temperature above the Af point (°C) calculated by the following formula (I) for 20 to 3000 seconds, cooled to below 100°C, and pickled after the annealing to produce a pickled steel plate.
[0055] (c) A cold rolling process, wherein the pickled steel sheet is cold rolled at a reduction rate of 50% or more to produce a cold-rolled steel sheet; and
[0056] (d) Annealing process: The cold-rolled steel sheet is heated at a rate of 20°C / s or higher, held at a temperature of 0 to 30 s above the As point (°C) calculated by formula (II) below and below 900°C, and cooled at a cooling rate of 20°C / s or higher.
[0057] Af point(℃)=As point+100(℃)…(I)
[0058] It should be noted that point As in equation (I) above is obtained from equation (II) below.
[0059] As point (℃)=937.2-436.5C+56Si-19.7Mn-16.3Cu-26.6Ni-4.9Cr+38.1Mo+124.8V+136.3Ti-19.1Nb+198.4Al+3315B…(II)
[0060] (5) A method for manufacturing a stainless steel plate, comprising the following steps in sequence:
[0061] (a) A process of heating a slab having the chemical composition described in (1) or (2) above in the range of 1100 to 1300 degrees Celsius and hot rolling it to produce a hot-rolled steel plate.
[0062] (b) The hot-rolled steel plate annealing process is carried out as follows: the hot-rolled steel plate is held at an annealing temperature above the Af point (°C) calculated by the following formula (I) for 20 to 3000 seconds, cooled to below 100°C, and pickled after the annealing to produce a pickled steel plate.
[0063] (c) A cold rolling process, wherein the pickled steel sheet is cold rolled at a reduction rate of 50% or more to produce a cold-rolled steel sheet; and
[0064] (d) Annealing process: The cold-rolled steel sheet is heated at a rate of 20°C / s or higher, held at a temperature above the As point (°C) calculated by formula (II) below for 0 to 30 seconds, and then cooled at a cooling rate of 20°C / s or higher.
[0065] In the hot rolling described in (a), the finishing rolling start temperature is set to 1000~1100℃, the finishing rolling end temperature is set to 950℃~1000℃, and the coiling temperature is set to below 600℃.
[0066] In the hot-rolled plate annealing process of (b), the annealing temperature is set to below 1050°C.
[0067] In the cold rolling process of (c), the reduction rate is set to 80% or more.
[0068] Af point(℃)=As point+100(℃)…(I)
[0069] It should be noted that point As in equation (I) above is obtained from equation (II) below.
[0070] As point (℃)=937.2-436.5C+56Si-19.7Mn-16.3Cu-26.6Ni-4.9Cr+38.1Mo+124.8V+136.3Ti-19.1Nb+198.4Al+3315B…(II)
[0071] The effects of the invention
[0072] According to the present invention, it is possible to obtain a stainless steel sheet containing martensite and austenite phases, with a balance of strength and ductility and excellent toughness. Attached Figure Description
[0073] Figure 1 It is a graph showing the relationship between the area ratio of the austenitic phase and the strength-ductility balance (the product of tensile strength and total elongation).
[0074] Figure 2 This is a graph showing the relationship between the average grain size of the austenite phase and the strength-ductility balance (the product of tensile strength and total elongation). Detailed Implementation
[0075] The inventors have conducted various studies and obtained the following insights.
[0076] (a) While martensite has high strength, it has low ductility. Therefore, by including a certain amount of austenite phase, ductility can be improved. The inventors then discovered that when the proportion of austenite phase is 30% or more in terms of area ratio, a good balance between strength and ductility, as well as toughness, is achieved. Furthermore, it was found that not only including a certain amount of austenite phase, but also making the austenite phase fine, specifically, making the average grain size 2.0 μm or less, is also effective in improving the balance between strength and ductility, as well as toughness.
[0077] (b) Typically, martensitic stainless steels are softened by hot rolling and annealing to decompose the martensitic structure into ferrite and carbides, followed by cold rolling, and then annealing at a temperature below the As point to prevent martensite formation during cooling. This method is used to obtain a soft, workable structure dominated by ferrite, but it is difficult to obtain a certain amount of the desired fine austenite phase.
[0078] Therefore, it is preferable to perform cold rolling while maintaining a fully martensitic microstructure, i.e., a martensitic-dominated metallographic structure, before cold rolling, and then annealing at a temperature range where austenite phase is generated through diffusionless reverse phase transformation. Furthermore, the annealing temperature at this stage is preferably set to a lower temperature than usual. This allows for the acquisition of a desired amount of fine austenite phase.
[0079] (c) The rationale for setting these manufacturing conditions is based on the following mechanism. By heating a cold-rolled steel sheet with a martensitic matrix at a specified temperature, a diffusionless reverse phase transformation from martensite to austenite is generated. Normally, the phase transformation from martensite to austenite is a diffusion-induced phase transformation accompanied by atomic movement. On the other hand, in the steel sheet of this embodiment, by allowing the phase transformation to occur in a diffusionless phase transformation without atomic movement, the grain growth of the austenite phase can be suppressed, resulting in grain refinement. Furthermore, by cold-rolling a fully martensitic structure, a large amount of strain is introduced, promoting nucleation, which also contributes to the refinement of the austenite phase.
[0080] Furthermore, the fine austenitic phase exhibits excellent thermal stability, thus suppressing the phase transformation from austenite to martensite during the cooling process of annealing, ensuring the desired amount of austenitic phase.
[0081] One embodiment of the present invention is based on the above-described understanding. Hereinafter, the components of the stainless steel sheet of this embodiment will be described in detail.
[0082] 1. Chemical composition
[0083] The reasons for the limitations of each element are as follows. It should be noted that in the following explanation, the "%" for content refers to "mass %".
[0084] C: 0.005~0.200%
[0085] Carbon (C) has the effect of improving strength. Therefore, the C content is 0.005% or more. The C content is preferably 0.010% or more, more preferably 0.020% or more. However, if the C content is excessive, ductility and toughness will decrease. Therefore, the C content is 0.200% or less. The C content is preferably 0.150% or less, more preferably 0.100% or less.
[0086] Si: 0.05~2.50%
[0087] Silicon (Si) is an element with deoxidizing effects. Therefore, the Si content is 0.05% or more. Preferably, the Si content is 0.10% or more, more preferably 0.20% or more. However, if Si is present in excess, the single-phase temperature range of austenite narrows, the stability of the austenite phase decreases, and the area fraction of the austenite phase decreases. As a result, the strength-ductility balance is reduced. Therefore, the Si content is 2.50% or less. Preferably, the Si content is 1.80% or less, more preferably 1.50% or less.
[0088] Mn: 0.1~8.0%
[0089] Manganese (Mn) has the effect of improving strength. Furthermore, it expands the single-phase austenite region, stabilizing the austenite phase. Therefore, the Mn content is 0.1% or more. The Mn content is preferably 0.3% or more, more preferably 0.5% or more. However, if Mn is present in excess, hardenability is excessively improved, martensite forms excessively, and the amount of austenite phase decreases. As a result, the strength-ductility balance is reduced. Therefore, the Mn content is 8.0% or less. The Mn content is preferably 6.0% or less, more preferably 5.0% or less.
[0090] P: below 0.0800%
[0091] Phosphorus (P) is an element present as an impurity in stainless steel, reducing its strength and ductility. Therefore, the P content should be below 0.0800%. While it is preferable to minimize the P content, excessive reduction will increase refining costs; therefore, the P content is preferably above 0.0085%.
[0092] S: below 0.030%
[0093] Sulfur (S) is an element present as an impurity in stainless steel, forming sulfide inclusions that reduce corrosion resistance. Furthermore, S reduces hot workability and increases the susceptibility of hot-rolled steel sheets to end cracking. Therefore, the S content is 0.030% or less. The phosphorus (P) content is preferably minimized, but excessive reduction leads to increased refining costs; therefore, the S content is preferably 0.001% or more.
[0094] Cr: 12.0~20.0%
[0095] Chromium (Cr) improves the corrosion resistance of stainless steel. It also enhances hardenability. Therefore, the Cr content is 12.0% or more. Preferably, the Cr content is 12.5% or more, and more preferably 13.0% or more. However, if Cr is present in excessive amounts, the stability of the austenite phase decreases, and the amount of austenite phase decreases. As a result, the strength-ductility balance is reduced. Therefore, the Cr content is 20.0% or less. Preferably, the Cr content is 18.0% or less, and more preferably 17.0% or less.
[0096] Ni: ≥0.30% and <8.00%
[0097] Like Mn, Ni (nickel) is an element that stabilizes the austenite phase. It also improves hardenability. Therefore, the Ni content is 0.30% or more. Preferably, the Ni content is 0.50% or more, more preferably 0.70% or more. However, if Ni is present in excess, the amount of austenite phase decreases. As a result, the strength-ductility balance is reduced. Therefore, the Ni content is less than 8.00%. Preferably, the Ni content is 7.50% or less, more preferably 7.00% or less.
[0098] Mo: 0.01~1.00%
[0099] Mo (Mo) is an effective element for improving the corrosion resistance of martensitic structures. Therefore, the Mo content is 0.01% or more. Preferably, the Mo content is 0.05% or more, more preferably 0.10% or more. However, Mo is an element that stabilizes the ferrite phase; if the Mo content is excessive, the single-phase temperature range of austenite narrows, thereby reducing the amount of austenite phase. As a result, the strength-ductility balance is reduced. Therefore, the Mo content is 1.00% or less. Preferably, the Mo content is 0.90% or less, more preferably 0.80% or less.
[0100] Al: below 0.500%
[0101] Al (aluminum) has a deoxidizing effect. It also improves oxidation resistance. However, if Al is present in excess, the amount of inclusions increases, reducing strength and ductility. Therefore, the Al content is 0.500% or less. The Al content is preferably 0.450% or less, more preferably 0.010% or less, and even more preferably 0.005% or less. On the other hand, to obtain the above-mentioned effects, the Al content is preferably 0.001% or more.
[0102] N: 0.005~0.100%
[0103] Nitrogen (N) improves strength and corrosion resistance. Therefore, the N content is 0.005% or more. Preferably, the N content is 0.010% or more, more preferably 0.020% or more. However, if the N content is excessive, corrosion resistance decreases. Furthermore, the austenite content also decreases. Therefore, the N content is 0.100% or less. Preferably, the N content is 0.090% or less, more preferably 0.080% or less.
[0104] In addition to the elements mentioned above, the element may contain one or more elements selected from Ca, Cu, Ti, Nb, B, V, Sn, and Co within the range shown below. That is, the lower limit for the above elements is 0%. The rationale for these limitations is explained below.
[0105] Ca: 0~0.0100%
[0106] Ca (calcium) has a deoxidizing effect. Therefore, it can be included as needed. However, if Ca is present in excess, a large number of inclusions will form, which will easily reduce manufacturability. Therefore, the Ca content is 0.0100% or less. The Ca content is preferably 0.0090% or less, more preferably 0.0080% or less. On the other hand, in order to obtain the above-mentioned effect, the Ca content is preferably 0.0001% or more, more preferably 0.0002% or more, and even more preferably 0.0003% or more.
[0107] Cu: 0~7.0%
[0108] Cu (copper) is an element that improves strength. It also has the effect of stabilizing the austenite phase. Therefore, it can be included as needed. However, if Cu is present in excess, hot workability decreases. Therefore, the Cu content is 7.0% or less. The Cu content is preferably 6.5% or less, more preferably 6.0% or less. On the other hand, to obtain the above-mentioned effects, the Cu content is preferably 0.5% or more.
[0109] Ti: 0~0.70%
[0110] Titanium (Ti) forms carbonitrides, which improves corrosion resistance. Therefore, it can be included as needed. However, if Ti is present in excess, coarse TiN is formed, which easily leads to hot-rolling defects. In addition, toughness is easily reduced. Therefore, the Ti content is 0.70% or less. The Ti content is preferably 0.60% or less. More preferably 0.50% or less. On the other hand, in order to obtain the above-mentioned effects, the Ti content is preferably 0.05% or more.
[0111] Nb: 0~1.00%
[0112] Niobium (Nb) forms carbonitrides, resulting in a fine metallographic structure. This, in turn, improves strength. Therefore, it can be included as needed. However, excessive Nb content can easily reduce ductility. Therefore, the Nb content is 1.00% or less. Preferably, the Nb content is 0.90% or less, more preferably 0.80% or less. On the other hand, to obtain the above-mentioned effects, the Nb content is preferably 0.01% or more.
[0113] B: 0~0.0050%
[0114] Boron (B) has the effect of improving hot workability. Therefore, it can be included as needed. However, if B is present in excess, hardenability may sometimes decrease. Therefore, the B content is 0.0050% or less. The B content is preferably 0.0040% or less, more preferably 0.0030% or less. On the other hand, in order to obtain the above-mentioned effect, the B content is preferably 0.0005% or more.
[0115] V: 0~0.50%
[0116] Vanadium (V) forms fine carbonitrides, which improves corrosion resistance. Therefore, it can be included as needed. However, if V is present in excess, ductility and toughness tend to decrease. Therefore, the V content is 0.50% or less. The V content is preferably 0.45% or less, more preferably 0.40% or less. On the other hand, in order to obtain the above-mentioned effects, the V content is preferably 0.01% or more.
[0117] Sn: 0~0.10%
[0118] Tin (Sn) has the effect of improving corrosion resistance. Therefore, it can be included as needed. However, if Sn is present in excess, end cracks during hot rolling are promoted. Therefore, the Sn content is 0.10% or less. The Sn content is preferably 0.09% or less, more preferably 0.08% or less. On the other hand, in order to obtain the above-mentioned effect, the Sn content is preferably 0.02% or more.
[0119] Co: 0~0.30%
[0120] Co (cobalt) is an element that improves heat resistance. Therefore, it can be included as needed. However, since Co is expensive, excessive Co content leads to increased manufacturing costs. Therefore, the Co content is 0.30% or less. The Co content is preferably 0.10% or less, more preferably 0.05% or less. On the other hand, to obtain the above-mentioned effects, the Co content is preferably 0.01% or more.
[0121] The microstructure of stainless steel sheets is influenced by their chemical composition. It should be noted that the chemical composition is not particularly limited as long as the above-mentioned chemical composition is met. For example, to obtain the metallographic structure described later in this application, the following chemical composition is preferred. Specifically, to ensure that the metallographic structure before cold rolling annealing is the fully martensitic structure described later, the Cr equivalent is in the range of 10.0% to 20.0%, and the Ni equivalent is in the range of 5.0% to 15.0%. Furthermore, the Ms point is 50°C or higher.
[0122] It should be noted that the above-mentioned Cr equivalent can be calculated by equation (i) below. Additionally, the above-mentioned Ni equivalent can be calculated by equation (ii) below.
[0123] Cr equivalent (%) = Cr + Mo + 1.5Si + (0.5Nb)…(i)
[0124] Ni equivalent (%) = Ni + 30(C + N) + 0.5Mn + (0.3Cu)...(ii)
[0125] In the above formula, the symbols of each element represent the content (mass%) of each element contained in the stainless steel plate, and are set to zero if the element is not contained.
[0126] The Ms point mentioned above can be calculated using the following equation (iii).
[0127] Ms point (℃)=545-330(C+N)+Al+7Co-14Cr-13C-23Mn-5Mo-4Nb-13Ni-7Si+3Ti+4V…(iii)
[0128] In the above formula, the symbols of each element represent the content (mass%) of each element contained in the stainless steel plate, and are set to zero if the element is not contained.
[0129] The Ms point is the temperature at which the martensitic phase transformation begins during cooling. The Ms point, which becomes fully martensite before cooling is complete, is 50°C or higher. Preferably, the Ms point is 100°C or higher, and more preferably 200°C or higher.
[0130] It should be noted that in order to set the area ratio of the austenitic phase described later to the desired range while taking into account both strength and ductility, it is important to control the manufacturing conditions to a specified range. As long as the above chemical composition is satisfied, its chemical composition is not particularly limited. For example, it is preferable to set Md30, which is an indicator of the mechanical stability of the austenitic phase, to the range of 23 to 250°C.
[0131] The austenitic phase in steel sheets needs to undergo a work-induced phase transformation to become martensitic when subjected to work strain. The index for work-induced phase transformation is based on Md30, as shown in equation (iv) below. Md30 represents the temperature at which 50% of the γ phase transforms into work-induced martensite when a true strain of 0.3 is applied. The lower the Md30, the higher the mechanical stability and the less likely work-induced martensitic transformation will occur. At this point, by setting Md30 to room temperature (above 23°C), work-induced phase transformation occurs more easily, improving strength and ductility. It should be noted that Md30 is determined by the chemical composition, but if it is too high, the mechanical stability of austenite is excessively reduced, sometimes making it difficult to form austenite itself. Therefore, Md30 is preferably below 250°C.
[0132] It should be noted that the above Md30 (°C) can be calculated by the following formula (iv).
[0133] Md30(℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb…(iv)
[0134] In the above formula, the symbols of each element represent the content (mass%) of each element contained in the stainless steel plate, and are set to zero if the element is not contained.
[0135] In the chemical composition of this embodiment, the balance is Fe and impurities. Here, "impurities" refers to components that may be mixed in during the industrial manufacturing of stainless steel sheets due to various reasons such as raw materials (ore, waste, etc.) and manufacturing processes, and are permissible within a range that does not adversely affect this embodiment.
[0136] 2. Metallographic structure
[0137] In the stainless steel sheet of this embodiment, the metallographic structure includes martensite and austenite phases. It should be noted that the metallographic structure of the stainless steel sheet of this embodiment is basically composed of martensite and austenite phases, but in addition to austenite and martensite, it may also include precipitates such as δ-ferrite, inclusions, carbides, and intermetallic compounds. It should be noted that precipitates such as δ-ferrite, inclusions, carbides, and intermetallic compounds are collectively referred to as unavoidably formed structures.
[0138] 2-1. Area ratio of austenite phase
[0139] Figure 1 This is a graph showing the relationship between the area fraction of the austenite phase and the strength-ductility balance (the product of tensile strength and total elongation). Figure 1 It can be seen that when the area ratio of the austenite phase is above 30%, the balance between strength and ductility is improved, and the toughness is also improved. In addition, when the area ratio of the austenite phase is above 85%, the balance between strength and ductility is significantly improved, and the toughness is further improved.
[0140] On the other hand, in the stainless steel sheet of this embodiment, the area fraction of the austenite phase is less than 100%. This is because it contains martensite. Therefore, in the stainless steel sheet of this embodiment, the area fraction of the austenite phase is 30% or more and less than 100%.
[0141] From the viewpoint of achieving a good balance between strength and ductility, the area fraction of the austenitic phase is preferably 95% or less, more preferably 90% or less. It should be noted that the balance other than the austenitic phase is preferably martensite, but for the aforementioned unavoidable formation of microstructure, if it is 5% or less in terms of area fraction, it will not adversely affect the properties of the stainless steel sheet of this embodiment, and therefore is permissible.
[0142] 2-2. Average grain size of austenite phase
[0143] Figure 2 This is a graph showing the relationship between the average grain size of the austenite phase and the strength-ductility balance (the product of tensile strength and total elongation). Figure 2 It is known that when the average grain size of the austenite phase is 2.0 μm or less, the desired balance between strength and ductility can be achieved. On the other hand, when the average grain size of the austenite phase exceeds 2.0 μm, the toughness decreases. Therefore, in the stainless steel sheet of this embodiment, the average grain size of the austenite phase is 2.0 μm or less.
[0144] The average grain size of the austenite phase is preferably 1.5 μm or less, more preferably 1.0 μm or less, 0.8 μm or less, or 0.5 μm or less. Furthermore, especially when improving toughness is desired, the average grain size of the austenite phase is preferably 1.5 μm or less. It should be noted that the lower limit of the average grain size of the austenite phase is not particularly limited; considering the manufacturing conditions described later, it is 0.1 μm.
[0145] The observation and measurement of the metallographic structure can be performed according to the following steps. Prepare the sample with the C-section of the steel plate (a section parallel to the thickness direction and perpendicular to the rolling direction) as the observation plane, and perform measurements using SEM and the EBSD attached to the SEM. First, use an optical microscope or SEM to look for characteristic structures such as lath structure to confirm the presence or absence of martensite. Next, use the EBSD attached to the SEM to identify the grains of the austenite phase with the FCC structure. Analyze the obtained measurement data using the OIM4.0-CCD / ADV crystal orientation analysis system (manufactured by TSL Solutions), and use the percentage (%) obtained by dividing the area of the austenite grains by the measurement range as the austenite phase area ratio. Additionally, calculate the average grain size from the grains identified as austenite. The SEM-EBSD measurement conditions are set to a magnification of 5000x, a step size of 0.07 μm, and a measurement range of 18 × 52 μm.
[0146] 3. Characteristics as a target
[0147] The stainless steel sheet of this embodiment is considered to have a good balance between strength and ductility if the product of its tensile strength (MPa) and total elongation (%) is 12000 or more. Preferably, the product of its tensile strength (MPa) and total elongation (%) is 14000 or more.
[0148] The determination of tensile strength and total elongation can be performed according to the following steps: Prepare a JIS 13B tensile test piece with the rolling direction aligned with the length direction, conduct a tensile test, and determine the tensile strength and total elongation. It should be noted that the stress rise rate up to the yield point is set to 10 N / (mm). 2 After reaching the yield point (·s), the tensile speed is set to 25 mm / min. It should be noted that the point at which 0.2% strain is produced is considered the yield point. Other test conditions should conform to JIS Z 2253:2020.
[0149] If the Charpy impact value of the stainless steel plate in this embodiment is 130 J / cm 2 The above indicates good toughness. A Charpy impact value of 150 J / cm is preferred. 2 above.
[0150] The Charpy impact value is determined according to the following steps: Collect a 3mm thick Charpy test piece with a notch from a direction parallel to the rolling direction. The test is conducted at 25°C (room temperature) according to JIS Z 2242:2023 to determine the Charpy impact value.
[0151] 4. Manufacturing method
[0152] The stainless steel sheet of this embodiment can be stably manufactured, for example, by a manufacturing method including a hot rolling process, a hot-rolled sheet annealing process, a cold rolling process, and a cold-rolled sheet annealing process. In order to increase the area ratio of the austenite phase, especially to make it exceed 85%, (1) a metallographic structure is prepared up to the cold rolling process, and (2) the reduction rate in the cold rolling process is increased. Specifically, as for the preparation of the metallographic structure up to the cold rolling process (1), as described later, the finishing rolling temperature and coiling temperature of the hot rolling are set to low temperatures, and the annealing temperature of the hot-rolled sheet is set to low temperatures. As a result, a large amount of strain can be introduced in the hot rolling. By annealing the hot-rolled sheet with this high-strain hot-rolled structure under the conditions described later, the austenite nucleation in the hot-rolled sheet annealing can be promoted and grain growth can be suppressed, thereby refining the structure before cold rolling. (2) A higher cold rolling strain than usual is introduced by cold rolling the refined structure. In addition, by performing cold rolling with a sufficiently high reduction rate described later, a large amount of strain can be introduced. Furthermore, by performing cold-rolled sheet annealing on the high-strain metallographic structure obtained by (1) and (2) above, the austenite phase transformation can be promoted, the austenite grains can be sufficiently refined, and the area ratio of the austenite phase can exceed 85%.
[0153] 4-1. Hot rolling process
[0154] Steel having the above-mentioned chemical composition is smelted to produce billets (slabs, etc.) for hot rolling, such as castings. In the steel plate manufacturing method of this embodiment, for example, a slab obtained by continuous casting after smelting is heated in the range of 1100 to 1300°C and hot rolled to produce a hot-rolled plate.
[0155] In addition, to ensure that the area ratio of the austenite phase in the microstructure after cold rolling and annealing exceeds 85%, the finishing rolling start temperature is set to 1000~1100℃, the finishing rolling end temperature is set to 950~1000℃, and the coiling temperature is set below 600℃ during the hot rolling process. There is no specific limitation on the lower limit of the coiling temperature; it can be set above 500℃.
[0156] 4-2. Annealing process of hot-rolled sheet
[0157] The obtained hot-rolled sheet is annealed. In the steel sheet manufacturing method of this embodiment, the hot-rolled sheet is annealed before cold rolling to make the metallographic structure of the steel sheet a fully martensitic structure, that is, a structure with a martensite area ratio of 95% or more. Usually, in the manufacturing of steel sheets containing martensite, the martensite is decomposed into ferrite phase and carbides and softened before cold rolling. This is because if cold rolling is performed directly with a hard and brittle metallographic structure such as martensite, the load during cold rolling is large, and the yield is easily reduced.
[0158] On the other hand, in the steel sheet of this embodiment, since it is necessary to obtain a fine and sufficient amount of austenitic phase, a fully martensitic structure is formed before cold rolling. This is because by forming such a metallographic structure, a large amount of strain can be introduced during cold rolling, and a fine and sufficient amount of austenitic phase can be effectively obtained through subsequent cold-rolled sheet annealing, etc.
[0159] Therefore, hot-rolled sheet annealing involves holding the sheet at a temperature above the Af point (°C) and below 1200°C for 20 to 3000 seconds and then cooling it to below 100°C. This is because if the annealing temperature is set above the Af point (°C) and below 1200°C, and then cooled to below 100°C, the aforementioned fully martensitic structure can be obtained. Furthermore, this is because if the holding time at the annealing temperature during hot-rolled sheet annealing is in the range of 20 to 3000 seconds, the aforementioned fully martensitic structure can also be obtained after cooling. Moreover, in order to ensure that the area ratio of the austenite phase in the metallographic structure of the annealed cold-rolled sheet exceeds 85%, the annealing temperature in the hot-rolled sheet annealing process is further preferably below 1050°C.
[0160] After annealing, the hot-rolled sheet undergoes appropriate pickling. Furthermore, the As point (°C) and Af point (°C) can be calculated using the formulas described later.
[0161] 4-3. Cold rolling process
[0162] A cold-rolled sheet is manufactured by cold rolling a hot-rolled sheet that has undergone annealing and cooling. The reduction rate during cold rolling is preferably 50% or more, more preferably 70% or more. This is because a reduction rate of 50% or more during cold rolling allows for the introduction of sufficient strain into the martensitic structure. Furthermore, to ensure that the area fraction of the austenite phase in the metallographic structure of the annealed cold-rolled sheet exceeds 85%, the reduction rate during the cold rolling process is further preferably 80% or more. It should be noted that, in order to achieve the above-mentioned reduction range, the sheet thickness of the steel sheet in this embodiment is in the range of 3.0 to 0.1 mm. It should also be noted that other conditions during cold rolling are not particularly limited and can be performed using conventional methods.
[0163] 4-4. Annealing of cold-rolled sheet (final annealing)
[0164] The obtained cold-rolled sheet is annealed. This annealing is referred to as cold-rolled sheet annealing or final annealing. The phase transformation strain of the martensite generated during hot-rolled sheet annealing and the large amount of processing strain introduced during cold rolling serve as driving forces to promote the nucleation of austenite in the cold-rolled sheet annealing, resulting in very fine austenite grains of 2.0 μm or less. Regarding the annealing temperature in the cold-rolled sheet annealing, it is generally set to 1000°C or higher for steel sheets containing martensite. On the other hand, in the steel sheet manufacturing method of this embodiment, in order to suppress the grain growth of the austenite phase, a relatively low annealing temperature is preferably set, in the range of As point (°C) or higher and 900°C or lower. This is because, by setting the annealing temperature within the above range, the reverse phase transformation from martensite to austenite can be promoted, and the grain growth of the austenite phase can be suppressed.
[0165] It should be noted that, in order to achieve the aforementioned microstructure refinement, the As point, which serves as the initiation temperature of the reverse phase transformation, needs to be set to the range of 650℃ to 850℃ through composition adjustments. At temperatures above 850℃, the diffusion of iron atoms at high temperatures is promoted, thus facilitating grain growth of the resulting fine austenite grains even during annealing at these temperatures. Conversely, when the As point is below 650℃, austenite nucleation does not occur, the phase transformation strain and cold rolling strain recover, and grain refinement sometimes becomes difficult.
[0166] The inverse phase transition end temperature, i.e., the Af point, can be calculated using equation (I) below. Additionally, the As point (°C) mentioned above can be calculated using equation (II) below.
[0167] Af point(℃)=As point+100(℃)…(I)
[0168] It should be noted that point As in equation (I) above is obtained from equation (II) below.
[0169] As point (℃)=937.2-436.5C+56Si-19.7Mn-16.3Cu-26.6Ni-4.9Cr+38.1Mo+124.8V+136.3Ti-19.1Nb+198.4Al+3315B…(II)
[0170] In the above formula, the symbols of each element represent the content (mass%) of each element contained in the stainless steel plate, and are set to zero if the element is not contained.
[0171] In addition, during the annealing of cold-rolled steel sheets, the holding time at the annealing temperature is set to a range of 0-20 seconds to suppress the growth of austenite grains. If the holding time at the annealing temperature exceeds 20 seconds, the holding time above the As point becomes longer, thus making it easier for austenite grains to grow. It should be noted that a holding time of 0 seconds at the annealing temperature means that cooling begins immediately upon reaching the annealing temperature.
[0172] Furthermore, heating to the annealing temperature is performed at a heating rate of 20°C / s or higher. By setting the heating rate within the aforementioned range, diffusion-induced phase transformation is suppressed, and a diffusionless reverse phase transformation without atomic movement readily occurs. At this time, by inheriting the processing strain introduced during cold rolling, the nucleation of austenite recrystallized grains is also promoted, resulting in finer austenite grains. Additionally, the area fraction of the austenite phase can be made 30% or more. The heating rate is preferably 20°C / s or higher, more preferably 100°C / s or higher.
[0173] To obtain finer austenitic grains, a heating rate of 300°C / s or higher is more preferable, and 400°C / s or higher is even more preferable. It should be noted that there is no particular upper limit to the heating rate; for example, from the viewpoint of manufacturing equipment, 2000°C / s is preferred.
[0174] Furthermore, after holding at the annealing temperature for 0 to 20 seconds, cooling is performed at a cooling rate of 20°C / s or higher. By setting the cooling rate within the aforementioned range, excessive grain growth can be suppressed. The cooling rate is preferably 40°C / s or higher, more preferably 50°C / s or higher. Then, it is preferable to cool to below 400°C. After cooling, pickling or other appropriate processes can be performed.
[0175] It should be noted that, in the manufacturing methods described above, for conditions not specifically mentioned, conventional methods can be followed appropriately.
[0176] The stainless steel plate of the present invention will be described in more detail below through embodiments, but the embodiments are not limited to these embodiments.
[0177] Example 1
[0178] Steel with the chemical composition shown in Table 1 is smelted to produce hot-rolled billets. The obtained hot-rolled billets are heated at 1200°C and hot-rolled to produce hot-rolled sheets. The obtained hot-rolled sheets are annealed under the conditions shown in Table 2, cooled to room temperature, pickled, and then cold-rolled under the conditions shown in Table 2 to produce cold-rolled sheets. The obtained cold-rolled sheets are annealed under the conditions shown in Table 2, cooled to room temperature, and pickled to obtain stainless steel sheets with a thickness of 1.0 mm. It should be noted that martensite is included in all examples. It should be noted that the cooling rates in the table are the cooling rates from the cold-rolled sheet annealing temperature to 400°C.
[0179] [Table 1]
[0180]
[0181] [Table 2]
[0182]
[0183] The area ratio and average grain size of the austenite phase in the obtained stainless steel sheet were determined according to the following steps. Furthermore, a tensile test was performed on the obtained steel sheet to determine the tensile strength and total elongation (%). Additionally, a Charpy impact test was performed to determine the Charpy impact value.
[0184] (Area ratio and average grain size of austenite phase)
[0185] Samples were prepared with the C-section of the steel plate (parallel to the thickness direction and perpendicular to the rolling direction) as the observation plane, and measurements were performed using SEM and the EBSD attached to the SEM. First, SEM was used to identify characteristic microstructures such as lath structure to confirm the presence or absence of martensite. Next, the EBSD attached to the SEM was used to identify austenite grains with an FCC structure. The obtained measurement data were analyzed using an OIM4.0-CCD / ADV crystal orientation analysis system (manufactured by TSL Solutions), and the area of the austenite grains was divided by the measurement range (%) as the austenite phase area ratio. Additionally, the average grain size was calculated from the grains identified as austenite. The SEM-EBSD measurement conditions were set to a magnification of 5000x, a step size of 0.07 μm, and a measurement range of 18 × 52 μm.
[0186] (Tensile strength and total elongation)
[0187] Tensile test specimens conforming to JIS 13B standard were prepared from cold-rolled annealed sheets with the rolling direction aligned with the length direction. Tensile tests were then conducted to determine the tensile strength and total elongation. It should be noted that the stress rise rate up to the yield point was set to 10 N / (mm²). 2 After the yield point (·s), the tensile speed is set to 25 mm / min. It should be noted that the point at which 0.2% strain is produced is considered the yield point. Other test conditions are in accordance with JIS Z 2253:2020.
[0188] (Charpy Impact Value)
[0189] Charpy test pieces (3 mm thick) with a notch were collected from cold-rolled annealed sheets from a direction parallel to the rolling direction. For these test pieces, Charpy tests were conducted at 25°C (room temperature) according to JIS Z 2242:2023 to determine the Charpy impact value.
[0190] [Table 3]
[0191]
[0192] Examples a1 to a21 of the present invention, which satisfy the requirements of this embodiment, have good strength-ductility balance and toughness. On the other hand, comparative examples a1 to a17, which do not satisfy the requirements of this embodiment, have poor strength-ductility balance and / or toughness. In particular, in examples a20 and a21 of the present invention, the area ratio of the austenite phase exceeds 85%, the average grain size of the austenite phase is 1.0 μm or less, and both the strength-ductility balance and toughness are excellent.
[0193] Example 2
[0194] For steel grades A17 and A18 in Table 1, steel sheets with a thickness of 3 mm were manufactured from 6.2 mm hot-rolled sheets through hot-rolling annealing, cold rolling, and cold-rolling annealing, using the manufacturing conditions described in Table 4. Other conditions were the same as in Example 1. The obtained steel sheets were evaluated using the same items (area ratio of austenite phase, average grain size of austenite phase) and properties as in Example 1. The measurement methods were the same.
[0195] [Table 4]
[0196]
[0197] Charpy impact value and toughness improve when the average grain size of the austenite phase is below 1.5 μm. Particularly when the austenite phase area fraction is above 40% or the average grain size of the austenite phase is below 1.0 μm, the Charpy impact value reaches 200 J / cm². 2 The above makes things better, and consequently, it makes them more resilient.
Claims
1. A stainless steel plate, the chemical composition of which is (in mass%) as follows: C:0.005~0.200%、 Si: 0.05~2.50% Mn: 0.1~8.0%, P: Below 0.0800% S: Below 0.030% Cr:12.0~20.0%、 Ni: ≥0.30% and <8.00% Mo: 0.01~1.00% Al: Below 0.500% N:0.005~0.100%、 Ca: 0~0.0100% Cu: 0~7.0%, Ti: 0~0.70%, Nb: 0~1.00% B:0~0.0050%、 V:0~0.50%、 Sn: 0~0.10% Co: 0~0.30%, Balance: Fe and impurities, The Cr equivalent calculated by equation (i) below is 10.0~20.0%. The Ni equivalent calculated by equation (ii) below is 5.0% to 15.0%. The Ms point calculated by equation (iii) below is above 50℃. The metallographic structure contains martensite and austenite phases. The area fraction of the austenite phase is greater than 30% and less than 100%. The average grain size of the austenite phase is less than 2.0 μm. Cr equivalent = Cr + Mo + 1.5Si + (0.5Nb)…(i) Ni equivalent = Ni + 30(C + N) + 0.5Mn + (0.3Cu)...(ii) Ms point (℃)=545-330(C+N)+Al+7Co-14Cr-13C-23Mn-5Mo-4Nb-13Ni-7Si+3Ti+4V…(iii), in, The symbols for each element in the above formula represent the content of each element in stainless steel by mass%, and are set to zero if the element is not present.
2. The stainless steel plate according to claim 1, wherein, The chemical composition, expressed in % by mass, contains ingredients selected from... Ca: 0.0001~0.0100% Cu: 0.5~7.0%, Ti: 0.05~0.70%, Nb: 0.01~1.00% B:0.0005~0.0050%、 V:0.01~0.50%、 Sn: 0.02~0.10%, and Co: 0.01% to 0.30% of one or more of the following.
3. The stainless steel plate according to claim 1 or 2, wherein, The area fraction of the austenitic phase is over 85%.
4. A method for manufacturing a stainless steel plate, comprising the following steps in sequence: (a) A process of heating a slab having the chemical composition of claim 1 or 2 in the range of 1100 to 1300 degrees Celsius and hot rolling it to produce a hot-rolled steel plate. (b) The hot-rolled steel plate annealing process is carried out as follows: the hot-rolled steel plate is held at an annealing temperature above the Af point calculated by the following formula (I) for 20~3000s, cooled to below 100°C, and pickled after the annealing to produce a pickled steel plate, wherein the unit of Af point is °C. (c) A cold rolling process, wherein the pickled steel sheet is cold rolled at a reduction rate of 50% or more to produce a cold-rolled steel sheet; and (d) Annealing process: The cold-rolled steel sheet is heated at a rate of 20°C / s or higher, held at a temperature above the As point calculated by formula (II) below for 0 to 30 seconds, and cooled at a cooling rate of 20°C / s or higher, where the As point is in °C. Af point(℃)=As point+100(℃)…(I) It should be noted that point As in equation (I) above is obtained from equation (II) below. As point (℃)=937.2-436.5C+56Si-19.7Mn-16.3Cu-26.6Ni-4.9Cr+38.1Mo+124.8V+136.3Ti-19.1Nb+198.4Al+3315B…(II).
5. A method for manufacturing a stainless steel plate, comprising the method for manufacturing the stainless steel plate of claim 3, comprising the following steps in sequence: (a) A process of heating a slab having the chemical composition described in (1) or (2) above in the range of 1100 to 1300 degrees Celsius and hot rolling it to produce a hot-rolled steel plate. (b) The hot-rolled steel plate annealing process is carried out as follows: the hot-rolled steel plate is held at an annealing temperature above the Af point calculated by the following formula (I) for 20~3000s, cooled to below 100°C, and pickled after the annealing to produce a pickled steel plate, wherein the unit of Af point is °C. (c) A cold rolling process, wherein the pickled steel sheet is cold rolled at a reduction rate of 50% or more to produce a cold-rolled steel sheet; and (d) Annealing process: The cold-rolled steel sheet is heated at a rate of 20°C / s or higher, held at a temperature above the As point calculated by formula (II) below for 0 to 30 seconds, and cooled at a cooling rate of 20°C / s or higher, where the As point is in °C. In the hot rolling described in (a), the finishing rolling start temperature is set to 1000~1100℃, the finishing rolling end temperature is set to 950℃~1000℃, and the coiling temperature is set to below 600℃. In the hot-rolled plate annealing process of (b), the annealing temperature is set to below 1050°C. In the cold rolling process described in (c), the reduction rate is set to 80% or higher. Af point(℃)=As point+100(℃)…(I) It should be noted that point As in equation (I) above is obtained from equation (II) below. As point (℃)=937.2-436.5C+56Si-19.7Mn-16.3Cu-26.6Ni-4.9Cr+38.1Mo+124.8V+136.3Ti-19.1Nb+198.4Al+3315B…(II).
Citation Information
Patent Citations
High strength dual-phase structure stainless steel sheet and method of producing the same
JP2015086405A
